2018
DOI: 10.18203/2320-1770.ijrcog20184499
|View full text |Cite
|
Sign up to set email alerts
|

Learning internal iliac artery ligation and pelvic ureter course through cadaveric dissections

Abstract: Background: Few surgical procedures, although vital, are not learnt and mastered during postgraduate courses in Obstetrics and Gynecology. Internal iliac artery ligation and tracing course of ureter are few of such surgical procedures. Cadaveric dissection sessions organized during postgraduate courses and as CME sessions (continued medical education) have proved useful in learning such unlearnt procedures. This article shares experiences from teaching internal iliac artery ligation, pelvic ureter course traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Despite its value, ligating the internal iliac artery is a skill that are not usually acquired in residency training mostly due to the infrequency of cases that require hypogastric artery ligation. Recently, Mahale et al ( 16 ) demonstrated the effectiveness of cadaver simulations on practicing hypogastric artery ligation and gaining the necessary skills to perform the procedure. Supporting their findings, we found that a significantly higher number of attendees were performing the procedure 1 year after the workshop along with other measures against postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its value, ligating the internal iliac artery is a skill that are not usually acquired in residency training mostly due to the infrequency of cases that require hypogastric artery ligation. Recently, Mahale et al ( 16 ) demonstrated the effectiveness of cadaver simulations on practicing hypogastric artery ligation and gaining the necessary skills to perform the procedure. Supporting their findings, we found that a significantly higher number of attendees were performing the procedure 1 year after the workshop along with other measures against postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%